Method for manufacturing hole transport layer, and hole transport layer
By using aromatic ether, aromatic halogen or fused ring aromatic compound solvents with flash points above 40°C, combined with inkjet and spin coating methods, the preparation problem of the perovskite solar cell mesoporous transport layer is solved, and large-area uniformity and high-efficiency photoelectric conversion are achieved.
Patent Information
- Application Number
- JP2023120968
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, the low flash point of the solvent chlorobenzene limits the large area and uniformity of the pore transport layer of perovskite solar cells, and it is difficult for traditional methods to achieve efficient pore transport layer preparation in the perovskite structure.
One or more aromatic compounds selected from aromatic ethers, aromatic halogens or have condensed rings are used as solvents, with a flash point of 40°C or higher, and the pore transport layer is prepared in a perovskite solar cell by inkjet method, combined with a spin coating method to achieve large area and selective coating.
The large area, uniformity and selective preparation of pore transport layers in perovskite solar cells is achieved, and the photoelectric conversion efficiency and stability are improved.
Smart Images

Figure 2025017757000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for fabricating a hole transport layer for a perovskite solar cell and to a hole transport layer fabricated by said method. [Background technology]
[0002] Solar cells generally use elements such as silicon, compound semiconductors, and organic semiconductors, but organic-inorganic hybrid solar cells (perovskite solar cells) are attracting attention because of their high light-harvesting ability and the ability to be made thin and reduce costs.
[0003] Perovskite solar cells are broadly classified into two types: an nip structure in which a transparent conductive film, an electron transport layer, a perovskite layer, and a hole transport layer are stacked in that order, and a pin structure in which a transparent conductive film, a hole transport layer, a perovskite layer, and an electron transport layer are stacked in that order.
[0004] Patent Document 1 discloses a hole transport material having a donor-acceptor-donor structure for a nip-structure perovskite solar cell. This hole transport material is configured so that the molecule constituting the acceptor portion contains an electron-accepting group such as a fluorene ring, and the molecule constituting the donor portion contains an electron-donating group such as a 4-(bis(4-methoxyphenyl)amino)phenyl group, thereby enhancing the push-pull effect within the molecule and improving the charge transfer characteristics within the molecule. Such hole transport materials have low solubility due to their large molecular weight, and chlorobenzene was used as the solvent for the solution used to prepare the hole transport layer on the perovskite layer.
[0005] Patent Document 2 discloses a polymer composed of at least one monomer selected from the group consisting of thiophenes having substituents at positions 3 and 4 as a hole transport material that can provide high photoelectric conversion efficiency and high stability in a pin-structure perovskite solar cell. A hole transport layer using this material is formed by immersing a substrate having a conductive film in a solution and carrying out electrochemical polymerization, making it possible to fabricate a large-area hole transport layer.
[0006] Patent Document 3 discloses a coating conversion type material (metal complex of a phthalocyanine compound or a porphyrin compound) that can be crystallized and insolubilized after film formation as a hole transport material that can provide high photoelectric conversion efficiency and high stability in a nip- or pin-structure perovskite solar cell. The coating conversion type material is insoluble in a coating solvent, but its precursor compound is soluble in a coating solvent. Therefore, a hole transport layer containing the coating conversion type material can be produced on a coating target by coating the precursor compound and then reacting it. This allows the use of wet film formation methods such as spin coating and inkjet methods, making it possible to produce a hole transport layer over a large area. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2023-46046 A [Patent Document 2] JP 2020-136571 A [Patent Document 3] Patent Publication No. 2022-149015 Summary of the Invention [Problem to be solved by the invention]
[0008] Chlorobenzene, which is used as a solvent for the hole transport layer in Patent Document 1, has a low flash point of 28°C, so a wet film formation method using an inkjet method cannot be used, and the hole transport material cannot be applied to a large area. Therefore, it is difficult to enlarge a solar cell using such a material.
[0009] In the method for producing a solar cell in Patent Document 2, a hole transport layer is produced and then a perovskite layer is produced. In contrast, in a solar cell having an nip structure, when a hole transport layer is produced on a perovskite layer using a similar method, a substrate having a perovskite layer needs to be immersed in a solution, which causes dissolution of the perovskite layer and penetration of the solvent, resulting in a significant decrease in photoelectric conversion efficiency. Therefore, the production of a hole transport layer using electropolymerization has been limited to perovskite solar cells having a pin structure.
[0010] Furthermore, Patent Document 3 does not disclose details of the wet film formation method, and it is unclear how to uniformly form the hole transport layer.
[0011] In order to solve the above problems of the conventional technology, there is a need for a method for producing a large-area and uniform hole transport layer in a nip-structure perovskite solar cell, and a need for a solar cell having a hole transport layer produced by this method and having high photoelectric conversion efficiency. [Means for solving the problem]
[0012] A method for producing a hole transport layer of a solar cell having a perovskite compound according to the present invention is characterized in that it comprises the steps of: dissolving a hole transport material in a solvent having a flash point of 40° C. or higher and containing one or more selected from the group consisting of aromatic ethers, aromatic halides, and aromatic compounds having a condensed ring with an aliphatic ring; applying the solution containing the hole transport material to the surface of a perovskite layer; and drying the solution.
[0013] A method for producing a hole transport layer of a solar cell having a perovskite compound includes the steps of dissolving a hole transport material in a solvent containing at least one selected from aromatic ethers, aromatic halides, and aromatic compounds having a condensed ring with an aliphatic ring, and having a flash point of 40° C. or higher, applying the solution in which the hole transport material is dissolved to the perovskite layer, and drying the solution, thereby producing a hole transport layer on the perovskite layer. In particular, since the flash point of the solvent is 40° C. or higher, in addition to the solution application method using the spin coating method, the solution can be applied using the inkjet method, and a hole transport layer can be produced in a large area. Furthermore, since the solution can be selectively applied using the inkjet method, it is also possible to partially produce a hole transport layer on the perovskite layer. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of a perovskite solar cell. [Diagram 2] FIG. 1 is an explanatory diagram of power generation in a perovskite solar cell. [Diagram 3] FIG. 1 is an explanatory diagram showing a procedure for producing a perovskite solar cell. [Figure 4] 1 is a micrograph of the hole transport layer of Example 3. [Diagram 5] 1 is a micrograph of the hole transport layer of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the method for producing a hole transport layer according to the present invention will be described with reference to the drawings. In this embodiment, a hole transport layer of a solar cell having a perovskite compound will be described as an example of the hole transport layer. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the present invention.
[0016] [Basic structure of solar cell] As shown in FIG. 1, the solar cell 10 according to this embodiment includes a substrate 2 having a transparent substrate 21 and a transparent conductive film 22, an electron transport layer 3, a perovskite layer 4, a hole transport layer 5, and an electrode 6, which are sequentially formed into a laminate 11. The perovskite layer 4 is provided on the electron transport layer 3, and is excited by light to generate electrons and holes. The electron transport layer 3 is composed of a dense layer 32 and a porous layer 33, and transfers electrons to the transparent conductive film 22, and separates the hole transport layer 5 from the transparent conductive film 22 to prevent recombination of electrons and holes (reverse electron transfer). The electrode 6 includes a photoelectrode 61 provided on the surface of the transparent conductive film 22, and a counter electrode 62 provided on the surface of the hole transport layer 5. The electrons transferred to the transparent conductive film 22 move to the photoelectrode 61. The hole transport layer 5 transports holes generated in the perovskite layer 4 to the counter electrode 62. The electrons emitted from the photoelectrode 61 are received by the counter electrode 62. The arrangement of the electrode 6 is not particularly limited as long as it allows the transfer of electrons; for example, the photoelectrode 61 may be formed by connecting it to the electron transport layer 3 with a conductor. To increase the durability of the solar cell 10, the counter electrode 62 may be protected by a transparent substrate 21 or the like.
[0017] The transparent substrate 21 is made of a material having optical transparency, and may be, for example, a transparent glass substrate, a frosted semi-transparent glass substrate, a transparent resin substrate, etc. The transparent conductive film 22 may be, for example, fluorine-doped tin oxide (FTO), tin oxide (TO), tin-doped indium oxide (ITO), zinc oxide (ZnO), aluminum-doped zinc oxide (AZO), etc.
[0018] The electron transport layer 3 consisting of the dense layer 32 and the porous layer 33 is preferably made of a metal oxide, such as titanium dioxide (TiO2), zinc oxide (ZnO), niobium oxide (Nb2O5), tin dioxide (SnO2), or aluminum oxide (Al2O3). In particular, it is preferable to configure it as a sintered body of titanium dioxide (TiO2) that can secure a large surface area for stacking the perovskite layer 4. In addition, the dense layer 32 is formed by extending a part of it into the transparent conductive film 22, partitioning the transparent conductive film 22 and forming the insulating layer 31. In the dense layer 32, electrons can pass in the stacking direction, but the insulating layer 31 suppresses the movement of electrons in the lateral direction. In other words, the electrons that have entered from the electron transport layer 3 move smoothly in the stacking direction of the transparent conductive film 22 and are supplied to the photoelectrode 61, and the movement to the counter electrode 62 is prevented by the insulating layer 31, so that no short circuit occurs.
[0019] The perovskite layer 4 is a compound having a three-dimensional structure represented by the general formula ABX3, or a compound having a three-dimensional structure represented by the general formula A2BX4 or the general formula A (n+1) B n X (3n+1) It is sufficient that the perovskite compound has a two-dimensional structure represented by the formula (n=1 to 4), where A represents a monovalent cation, B represents a divalent cation, and X represents a monovalent anion.
[0020] The monovalent cation A can be an alkali metal cation or an organic molecular cation. Examples include cesium ion, rubidium ion, potassium ion, methylammonium ion, ethylammonium ion, propylammonium ion, butylammonium ion, pentylammonium ion, and hexylammonium ion. The cation A can also be a combination of two or more cations.
[0021] The divalent cation B may be a divalent metal cation or semimetal cation. Examples include lead cation, tin cation, germanium cation, etc. These may be used alone or in combination of two or more.
[0022] The monovalent anion X may be a halide ion. Examples of the anion include a fluoride ion, a chloride ion, a bromide ion, and an iodide ion. These may be used alone or in combination of two or more.
[0023] The perovskite layer 4 is produced, for example, by reacting a compound (PbX2, X = halogen element) composed of lead and halogen element X with methylammonium iodide (CH3NH3I: hereinafter sometimes abbreviated as "MAI"). Specifically, a solution containing lead and halogen element X is permeated into the pores of the porous layer 33, dried, and then immersed in a mixed solution of MAI, whereby crystals of the perovskite compound (CH3NH3PbI3 when X = I) that forms the perovskite layer 4 are rapidly produced. Note that, although iodine, bromine, chlorine, etc. can be used as the halogen element X, it is preferable to use iodine, which has high morphological stability. In addition, mixed cation-mixed halide (FAPbI3) was prepared using methylamine hydrobromide (CH5N·HBr, hereafter sometimes abbreviated as "MABr") and 0.2 M lead bromide (PbBr2), and formamidine hydroiodide (CH4N2·HI, hereafter sometimes abbreviated as "FAI") and lead iodide (PbI2). 1-x (MAPbBr3) x ) can also be used. For example, (FAPbI3) 0.85 (MAPbBr3) 0.15 etc. can be suitably used.
[0024] The hole transport layer 5 is made of a hole transport material described later. In this embodiment, the hole transport layer 5 is made by applying a solution in which the hole transport material is dissolved onto the surface of the perovskite layer 4 by an inkjet method. The electrode 6 can be made of, for example, a simple metal or alloy of gold, platinum, silver, copper, or an oxide conductor such as fluorine-doped tin oxide (FTO) or tin-doped indium oxide (ITO).
[0025] [Solvent used in preparing the hole transport layer] As a solvent for dissolving the hole transport material, a solvent containing at least one selected from aromatic ethers, aromatic halides, and aromatic compounds having a condensed ring with an aliphatic ring, and having a flash point of 40° C. or higher can be used. The aromatic ether having a flash point of 40° C. or higher can be selected from benzene-based solvents substituted with one or more alkoxy groups (the alkoxy in the group is preferably an alkoxy having 1 to 4 carbon atoms, such as methoxy, ethoxy, propoxy, etc.). These solvents may be further substituted with halogens or alkyl groups, or the alkoxy group may be substituted with an alkyl group having an ether bond. Examples of such solvents include anisole, phenetole, propoxybenzene, isopropoxybenzene, butylphenyl ether, cyclopentyloxybenzene, cyclohexylphenyl ether, 2-methylanisole, 3-methylanisole, 4-methylanisole, 2,3-dihydrobenzofuran, 2-ethylanisole, 4-ethylanisole, chroman, 2-methyl-2,3-dihydrobenzofuran, 5,7-dibromo-2,3-dihydrobenzofuran, 4-propylanisole, 2-isopropylanisole, 4-isopropylanisole, 6-methoxy-1,2,3,4-tetrahydronaphthalene, 4-t-butylanisole, 2,5-dimethylanisole, 2,6-dimethylanisole, 3,5-dimethylanisole, 2-isopropyl-5-methylanisole, 2,3 ,5-trimethylanisole, 2-isopropyl-5-methylanisole, 2-fluoroanisole, 3-fluoroanisole, 4-fluoroanisole, 2-chloroanisole, 3-chloroanisole, 4-chloroanisole, 2-bromoanisole, 3-bromoanisole, 4-bromoanisole, 2-iodoanisole, 3-iodoanisole, 4-iodoanisole, 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,4-difluoroanisole, 3,5-difluoroanisole, 4-chloro-3-fluoroanisole, 2-chloro-5-fluoroanisole, 3-chloro-4-fluoroanisole, 2-chloro-4-fluoroanisole, 3-chloro-5-fluoroanisole, 2,4,6-trifluoroanisole, 2,3,5,6-tetrafluoroanisole, 3-chloro-2-methylanisole, 2-(trifluoromethyl)anisole, 3-(trifluoromethyl)anisole, 4-(trifluoromethyl)anisole, 4-bromo-3-methylanisole, 3-bromo-5-methylanisole, 4-bromo-2,6-dimethylanisole, 4-ethylphenetole, 4-chlorophenetole, 2-chlorophenetole, 1,3-dimethoxybenzene, 1,4-benzodioxane, 1,3-diethoxybenzene, 1,3-dipropoxybenzene, 2,2-dimethyl-1,3-benzodioxole, 1,2,4-trimethoxybenzene, 3,5-dimethoxytoluene, 2,5-dimethoxytoluene, α,α,4-trimethoxytoluene, 4-fluoro-1,2-dimethoxybenzene, 1-chloro-2,3-dimethoxybenzene, 4-bromo-1,2-dimethoxybenzene, 1-fluoro-2,4-dimethoxybenzene, 2-chloro-1,4-dimethoxybenzene, 2-bromo-1,4-methoxybenzene, 3-bromo-2,6-dimethoxytoluene, 6-bromo-1,4- Benzodioxane, 1-chloro-2,5-diethoxybenzene, 4-(methoxymethyl)anisole, benzyl methyl ether, isocromane, (ethoxymethyl)benzene, isochromane, 2-phenylethyl methyl ether, 1,4-bis(methoxymethyl)benzene, benzaldehyde dimethyl acetal, benzaldehyde diethyl acetal, 4-methyl-2-phenyl-1,3-dioxolane, 2-bromobenzaldehyde dimethyl acetal, 4-bromobenzaldehyde dimethyl acetal, 4-butylbenzaldehyde benzaldehyde dimethyl acetal, 4-chlorobenzaldehyde diethyl acetal, 2-bromobenzaldehyde diethyl acetal, 3-bromobenzaldehyde diethyl acetal, 4-bromobenzaldehyde diethyl acetal, trimethyl orthobenzoate, triethyl orthobenzoate, 2-phenyl-1,3-dioxolane, 2-benzyl-1,3-dioxolane, 4-phenyl-1,3-dioxane, 2-benzyl-1,3-dioxane, dibenzyl ether, (2,2-dimethoxyethyl)benzene, 1,Examples of the solvent include 3-bis(methoxymethoxy)benzene, 2-phenoxytetrahydropyran, diphenoxymethane, diethylphenyl orthoformate, 1-methoxynaphthalene, 1-methoxy-4-methylnaphthalene, 1-ethoxynaphthalene, and 1-(methoxymethoxy)naphthalene. Considering the drying temperature of the hole transport layer 5, the flash point of the solvent is preferably 120° C. or lower, and more preferably 100° C. or lower. Therefore, solvents such as anisole, phenetole, 2-methylanisole, 3-methylanisole, and 4-methylanisole are suitable.
[0026] The aromatic halide having a flash point of 40° C. or more can be selected from benzene-based solvents substituted with one or more halogens. These solvents may be further substituted with an alkyl group or the like. Examples of such solvents include bromobenzene, iodobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2-dibromobenzene, 1,3-dibromobenzene, 1,4-dibromobenzene, 1,2,3-trifluorobenzene, 1,3,5-trifluorobenzene, 1,3,4-trifluorobenzene, 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2-chlorotoluene, 3-chlorotoluene, 4-chlorotoluene, 2-bromotoluene, 3-bromotoluene, 2-iodotoluene, and 3-iodotoluene. Considering the drying temperature of the hole transport layer 5, the flash point of the solvent is preferably 120° C. or less, and more preferably 100° C. or less. Therefore, suitable solvents include bromobenzene, 2-dichlorobenzene, 3-dichlorobenzene, 4-dichlorobenzene, etc. Fluorobenzene, chlorobenzene, 1,2-difluorobenzene, etc. have a flash point of 40° C. or less, and are therefore excluded from the solvent according to this embodiment.
[0027] The aromatic compound having a condensed ring with an aliphatic ring and a flash point of 40° C. or higher is a compound in which at least one aliphatic ring and at least one aromatic ring are condensed. The aliphatic ring may be a saturated aliphatic ring or an unsaturated aliphatic ring, and for example, a cyclopentane ring, a cyclohexane ring, a cyclohexene ring, etc. can be selected. The aromatic ring may be, for example, a benzene ring, etc. These condensed compounds may be substituted with halogen, an alkyl group, etc. Examples of such solvents include tetralin, 1,2-dihydronaphthalene, 1,4-dihydronaphthalene, indane, 1-methylindane, 2-methylindane, 4-methylindane, 5-methylindane, 2,7-dimethylindane, 4,7-dimethylindane, indene, 1-methyl-1H-indene, 1-methyl-3H-indene, 2-methyl-1H-indene, 7-methyl-1H-indene, 1,2,3,4,5,6,7,8-octahydronaphthalene, and tetraphene. Considering the drying temperature of the hole transport layer 5, the flash point of the solvent is preferably 120° C. or lower, and more preferably 100° C. or lower. Therefore, solvents such as tetralin and indan are suitable.
[0028] The above solvents may be used alone or in combination of two or more.
[0029] [Hole Transport Materials] The hole transport material is not particularly limited as long as it is a compound that has a hole transport function and can be dissolved in the above-mentioned solvent. Examples of the hole transport material include, but are not limited to, organic compounds such as compounds having a spirobifluorene skeleton, compounds having a phthalocyanine skeleton, compounds having a benzoporphyrin skeleton, and compounds having a donor-acceptor-donor type (hereinafter sometimes referred to as "DAD type") structure.
[0030] As a compound having a spirobifluorene skeleton, 2,2',7,7'-tetrakis(N,N'-di-p-methoxyphenylamino)-9,9'-spirobifluorene (commonly called "Spiro-OMeTAD"), which is widely used as a hole transport material, is preferable.
[0031] As a compound having a phthalocyanine skeleton, the compound described in JP 2017-066096 A is suitable, and is configured as a metal phthalocyanine complex in which a metal element such as zinc is coordinated at the center. This compound has a structure in which a substituent is introduced evenly at one β-position of each benzene ring portion in four indole rings constituting the phthalocyanine ring. In other words, a substituent is introduced at either the 2-position or the 3-position, either the 9-position or the 10-position, either the 16-position or the 17-position, or either the 23-position or the 24-position of the phthalocyanine ring. Examples of the substituent include thienyl groups having alkyl substitution such as 5-hexyl-thiophen-2-yl group and 5-(2-ethylhexyl)-thiophen-2-yl group (the alkyl in the group is preferably an alkyl having 6 to 8 carbon atoms), and also bis(4-alkoxyphenyl)amino group and 4-[bis(4-alkoxyphenyl)amino]phenyl group (the alkoxy in the group is preferably an alkoxy having 1 to 8 carbon atoms such as methoxy, ethoxy, propoxy, etc.), but are not limited thereto. In particular, the hole transport material is particularly preferably a compound represented by the following general formula 1.
[0032] [ka]
[0033] As a compound having a benzoporphyrin skeleton, the compound described in JP 2021-93433 A is suitable, and is configured as a metal tetrabenzoporphyrin complex in which a metal element such as zinc is coordinated at the center. This tetrabenzoporphyrin ring has a structure in which a substituent is introduced into the four meso positions. Examples of the substituent include a thienyl group having an alkyl substitution such as a 5-hexyl-thiophen-2-yl group or a 5-(2-ethylhexyl)-thiophen-2-yl group (the alkyl in the group is preferably an alkyl having 6 to 8 carbon atoms), and also a bis(4-alkoxyphenyl)amino group or a 4-[bis(4-alkoxyphenyl)amino]phenyl group (the alkoxy in the group is preferably an alkoxy having 1 to 8 carbon atoms such as methoxy, ethoxy, or propoxy), but are not limited thereto. In particular, the hole transport material is particularly preferably a compound represented by the following general formulas 2 to 4.
[0034] [ka] [ka] [ka]
[0035] A compound having a DAD structure is a compound in which a donor (D) portion containing an electron-donating group and an acceptor (A) portion containing an electron-withdrawing group are linked in the order of DAD.
[0036] The A part may be constituted by including a benzothiadiazole ring, a phenothiazine ring, a carbazole ring, a fluorene ring, a linear thiophene oligomer structure, or the like. Here, the nitrogen atom of the phenothiazine ring and the carbazole ring may be substituted with a hydrogen atom or an appropriate group. The appropriate group may preferably be a 4-alkoxyphenyl group, a bis(4-alkoxyphenyl)amino group, or a 4-[bis(4-alkoxyphenyl)amino]phenyl group (the alkoxy in the group is preferably an alkoxy having 1 to 8 carbon atoms, such as methoxy, ethoxy, or propoxy), but is not limited thereto. In addition, a 5-alkyl-2-thienyl group (the alkyl in the group is preferably an alkyl having 6 to 12 carbon atoms, such as hexyl, heptyl, octyl, or 2-ethylhexyl), or the same substituent as that in the D part described below, may be introduced to the carbon at the 9th position of the fluorene ring via a CC double bond. Furthermore, a bis(4-alkoxyphenyl) group (wherein the alkoxy in the group is preferably an alkoxy having 1 to 8 carbon atoms, such as methoxy or ethoxy) may be introduced at the 9-position of the fluorene ring. The linear thiophene oligomer structure is constituted by a linear thiophene oligomer structure in which unsubstituted or substituted thiophenes are linked at the 2-position (5-position), and is constituted as a poly(thiophene-2,5-diyl) group. Here, the number of repeating units of thiophene is preferably 2 to 9. When a substituent is present, an alkyl group having 1 to 12 carbon atoms, such as a hexyl group, is preferable.
[0037] As the D part, for example, those described in JP 2021-174977 A, JP 2023-46046 A, and JP 2023-46047 A are suitable. In detail, bis(4-alkoxyphenyl)amino group, 4-[bis(4-alkoxyphenyl)amino]phenyl group (note that the alkoxy in the group is methoxy, ethoxy, propoxy, etc.), 3,6-bis[N,N-bis(4-alkoxyphenyl)amino]-9H-carbazol-9-yl group (note that the alkoxy in the group is preferably an alkoxy having 1 to 8 carbon atoms such as methoxy, ethoxy, propoxy, etc.), etc. are exemplified, but are not limited to these. In addition, the D parts may be the same or different, but it is preferable to configure them as the same.
[0038] When the A part contains a benzothiadiazole ring, the D part is introduced at the 4th and 7th positions of the benzothiadiazole ring, when the A part contains a phenothiazine ring, the D part is introduced at the 3rd and 7th positions of the phenothiazine ring, and when the A part contains a carbazole ring, the D part is introduced at the 3rd and 6th positions of the carbazole ring. For example, the compounds described in JP-A-2021-174977 are suitable, but are not limited thereto. In particular, the hole transport material is particularly preferably a compound represented by the following general formulas 5 to 8.
[0039] [ka] [ka] [ka] [ka]
[0040] When the A moiety is composed of a fluorene ring, the D moiety is introduced at the 2-position and the 7-position of the fluorene ring, and for example, the compounds described in JP-A-2023-46046 and JP-A-2023-46047 are suitable, but are not limited to these. In particular, the hole transport material is particularly preferably a compound represented by the following general formulas 9 to 12.
[0041] [ka] [ka] [ka] [ka]
[0042] When the portion A is configured to include a thiophene oligomer structure, specifically, the hole transport material is particularly preferably a compound represented by the following general formula 13.
[0043] [ka]
[0044] Further, LD29 described in Xuepeng Liu et al., J. Mater. Chem. C., 2018, 6, 12912-12918 (DOI: 10.1039 / c8tc04191a), YN1 described in Peng Xu et al., ACS Appl. Mater. Interfaces 2018, 10, 23 (DOI: 10.1021 / acsami.8b04003), and PTZ2 described in Roberto Grisorio et al., ACS Energy Lett. 2017, 2, 5, 1029-1034 (DOI: 10.21 / acsenergylett.7b00054) can also be preferably exemplified.
[0045] Next, the principle of how the solar cell 10 generates electricity will be described with reference to FIG. 2. When light such as sunlight or room light is incident on the transparent substrate 21, the incident light is hardly absorbed and passes through the substrate 2 and the electron transport layer 3, and most of the incident light reaches the perovskite layer 4. When the incident light is irradiated onto the perovskite layer 4, the perovskite layer 4 absorbs the light energy and becomes excited. When the energy level of the perovskite layer 4 becomes higher than the conduction band potential of the metal oxide that is the porous layer 33 of the electron transport layer 3 by a predetermined level or more due to this excitation, electrons are injected from the perovskite layer 4 into the porous layer 33. The injected electrons are collected by the photoelectrode 61 via the dense layer 32.
[0046] On the other hand, holes generated in the perovskite layer 4 reach the counter electrode 62 via the hole transport layer 5, where they recombine with electrons that have passed through the external load 7. In other words, a potential gradient is generated between the photoelectrode 61 and the counter electrode 62, and therefore, by connecting the external load 7 between the two electrodes, electricity can be generated.
[0047] [Solar cell fabrication procedure] Next, a manufacturing procedure of the solar cell 10 according to this embodiment will be described with reference to FIG. 3. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the present invention. The solar cell 10 can be manufactured with reference to known techniques such as Michael Saliba et al., “Correction to “How to Make over 20% Efficient Perovskite Solar Cells in Regular (nip) and Inverted (pin) Architectures”, Chem. Mater., 2018, 30, 4193-4218, and the like.
[0048] [Preparation of Substrate and Electron Transport Layer] First, the transparent conductive film 22 is formed on the transparent substrate 21 to prepare the substrate 2. The transparent conductive film 22 is laminated on the transparent substrate 21 by, for example, CVD (chemical vapor deposition) or sputtering. Next, the transparent conductive film 22 is partially removed by laser scribing to form a recess 221 for the insulating layer 31, and then washed. Next, a dense layer 32 is formed on the entire surface of the substrate 2 by ALD (atomic layer deposition) or SPD (spray pyrolysis). The dense layer 32 is preferably formed as a TiO2 dense layer. Next, a porous layer 33, which is a nanoparticle sintered layer, is formed near the center of the masked substrate 2 and dense layer 32. It is preferably formed as a TiO2 porous layer 33 (p-TiO2). This porous layer 33 is formed by diluting the nanoparticle paste with a solvent, applying it by spin coating at a rotation speed of, for example, 4000 rpm to 6000 rpm, drying it, removing the masking, and heating it at 450° C. to 550° C. to sinter it.
[0049] [Preparation of perovskite layer] Next, for example, a solution of PbI2 in N,N-dimethylformamide is prepared and dropped onto the porous layer 33, and then the solution is permeated into the pores (p-TiO2) and excess solution is removed by spin coating at a rotation speed of, for example, 5000 rpm to 8000 rpm. Thereafter, the porous layer 33 is dried at 60°C to 120°C (preferably 70°C to 90°C) to form a PbI2 layer on the porous layer 33.
[0050] The substrate 2, dense layer 32, and porous layer 33 permeated with lead iodide are immersed in an isopropyl alcohol solution (2-20mg / ml) of methylammonium iodide (MAI) at 0°C to 80°C (preferably at room temperature) (MAI immersion method). PbI2 and MAI react to form a perovskite compound [(CH3NH3)PbI3(MAPbI3)] as a perovskite layer 4 inside and on the pores of the porous layer 33, and then the layer is flooded with a pure isopropyl alcohol solution and dried at 60°C to 120°C (preferably 70°C to 100°C). The mixed cation-mixed halide ((FAPbI3) 1-x (MAPbBr3) x) type perovskite compounds can be prepared in a similar manner.
[0051] In the above-mentioned manufacturing procedure, the crystal growth of the perovskite compound forming the perovskite layer 4 is controlled in two steps, but this may be performed in one step. For example, a perovskite ((CH3NH3)PbI3) solution is permeated into the pores of the porous layer 33 by spin coating. Toluene can be dropped during spinning to precipitate microcrystals and make the surface mirror-finished (poor solvent precipitation method).
[0052] [Preparation of Hole Transport Layer] The hole transport layer 5 is fabricated by carrying out a first step of dissolving a hole transport material in a solvent, a second step of applying the solution in which the hole transport material is dissolved, and a third step of drying the solution. In the first step of dissolving the hole transport material in a solvent, for example, anisole is used as a solvent to prepare an anisole solution of 60 to 90 mg / ml. The dilution concentration is preferably 1% by mass or more. If it is less than 1% by mass, the amount of solvent increases, so that it takes a long time to dry, and the film thickness becomes non-uniform due to localized volatilization of the solvent. In addition, the dilution concentration is preferably 5% by mass or less. If it is more than 5% by mass, the hole transport material becomes difficult to dissolve and cannot be applied. Therefore, the dilution concentration is preferably 1% by mass or more and 5% by mass or less.
[0053] The viscosity of the solution is preferably 1 to 10 mPa s. In the second coating step described below, if the viscosity of the solution is high, the droplets will not be able to wet and spread when they land on the surface of the perovskite layer 4, and a thin film will not be able to be formed.
[0054] Next, a second step is performed in which an anisole solution is applied to the surface of the perovskite layer 4. Since the flash point of the anisole according to this embodiment is 40° C. or higher, a wet film formation method using an inkjet method can be used in this second step. The inkjet head used in the inkjet method may be an on-demand type or a continuous type. In addition, any of a piezo type, a thermal type, and an electrostatic suction type can be used as a discharge method. In particular, the piezo type can accurately control the discharge amount of the solution by controlling the voltage. In addition, the piezo type is preferable because it is less affected by the usage environment since it does not require heating and has high durability.
[0055] In the second step of coating, the thickness of the wet film immediately after coating can be set appropriately, but is preferably 4 μm or less. If it is more than 4 μm, it takes a long time to dry the solvent, and the film thickness varies. Therefore, the wet film thickness is preferably 4 μm or less, and in particular, if it is 2 μm, the solvent is easily evaporated, making it easy to form a uniform film thickness, so that the effect of the present invention is more pronounced.
[0056] Furthermore, in the second coating step, it is preferable to repeatedly coat the solution in a number of separate steps. By repeatedly coating the solution, the film thickness can be increased. Furthermore, by repeatedly coating the wet film to a thickness of 4 μm or less, the solvent can be easily dried, so that a thin film having a uniform and required thickness can be obtained. In this second step, the solution can be repeatedly coated, for example, two to five times, but it may be coated only once.
[0057] Next, a third step of drying is performed. The drying temperature is preferably higher than the flash point of the solvent. If the drying temperature is lower than 50°C, the solvent is less likely to volatilize, which may cause film thickness variations. If the drying temperature is higher than 120°C, the hole transport material may decompose, significantly reducing the power generation efficiency of the solar cell 10. Therefore, the drying temperature is preferably 50°C or higher and 120°C or lower. If a highly volatile solvent is used, the third step of drying may be replaced by natural drying.
[0058] When the solution in which the hole transport material is dissolved is dried, the solvent evaporates completely, and only the hole transport material remains. Therefore, when a solution in which 5% by mass of the hole transport material is dissolved is applied so that the wet film has a thickness of 2 μm, the thickness of the thin film after drying is about 100 nm. In this way, the thickness of the thin film after drying can be determined from the amount of the hole transport material dissolved and the thickness of the wet film, so that the thickness of the hole transport layer 5 can be easily designed.
[0059] Finally, a thin film of gold or the like is attached to the surfaces of the electron transport layer 3 and the hole transport layer 5 by vacuum deposition or the like to form the electrode 6.
[0060] An example of how to fabricate the solar cell 10 will be described below. [Example] As an example, fluorine-doped tin oxide (FTO) glass (23 mm x 14 mm x 1.6 mm) was used for the transparent substrate 21. This FTO glass was laser scribed to form a recess 221 by removing the FTO, and was thoroughly washed. Next, a TiO2 dense film was formed as the dense layer 32 by spray pyrolysis (SPD). Furthermore, a solution of commercially available TiO2 nanoparticle paste diluted with ethanol was dropped, applied by spin coating, and dried at 100°C. After drying, the substrate was baked at 450°C to form a TiO2 nanoparticle layer that would become the porous layer 33. After baking, the substrate was cooled to room temperature.
[0061] Next, a perovskite precursor solution for forming the perovskite layer 4 was prepared. First, FAI (CH(NH2)2I) was weighed out, and a 1.7M solution of PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) that had been prepared in advance was poured into it to prepare a FAPbI3 solution. Next, MAI (CH3NH3I) was weighed out, and a 1.7M solution of PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) that had been prepared in advance was poured into it to prepare a MAPbI3 solution.
[0062] Finally, the FAPbI3 solution, the MAPbI3 solution, and a previously prepared 1.7 M CsI / dimethyl sulfoxide (DMSO) solution were mixed to prepare a precursor solution to be subjected to spin coating.
[0063] The perovskite layer 4 was formed by dropping the above-mentioned precursor solution onto the porous layer 33 on which the electron transport layer 3 was formed, and applying the solution by spin coating. After application was completed, the solution was heated at 100° C. for 60 minutes, and then cooled to room temperature.
[0064] Next, the hole transport layer 5 was prepared. As the hole transport material, a material called "DHCF-3" represented by the following general formula 14 was used. DHCF-3 was dissolved in anisole so that the final concentration of the solution was 5% by weight. Similarly, tetralin was selected as the solvent and tetralin was also dissolved to prepare a tetralin solution. Furthermore, 5% by weight of 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB) was added to these solutions to prepare hole transport layer solutions.
[0065] [ka]
[0066] Using a piezoelectric inkjet printer, the anisole solution was discharged onto the surface of the perovskite layer 4 under conditions that the thickness of the wet film from one application was 2 μm. The application area of the anisole solution was 50 mm × 100 mm. The anisole solution was then dried at 50 ° C for 3 to 5 minutes to obtain a hole transport layer 5 having a film thickness of 75 nm after drying. Under similar conditions, the second step of application was repeated two or four times to produce a solution coating. Similarly, the tetralin solution was discharged onto the surface of the perovskite layer 4 under conditions that the thickness of the wet film from one application was 2 μm, and the solution was dried at 120 ° C for 3 to 5 minutes to obtain a hole transport layer 5 having a film thickness of 75 nm after drying.
[0067] After the hole transport layer 5 was formed, a gold film of about 100 nm was formed by vacuum deposition, which was then removed to form the electrode 6, which was then laminated.
[0068] Next, the performance of the solar cell 10 was evaluated. Here, the solar cell 10 was fabricated and examined for one in which DHCF-3 was used as the hole transport material, anisole was used as the solvent for dissolving DHCF-3, and the hole transport layer 5 had a thickness of 75 nm (Example 1), and for one in which tetralin was used as the solvent for dissolving DHCF-3, and the hole transport layer 5 had a thickness of 75 nm (Example 2).
[0069] When the cell performance of the solar cell 10 was evaluated, the conversion efficiency of Example 1 was 15.1%, and the conversion efficiency of Example 2 was 6.90%, indicating that the hole transport layer 5 can be sufficiently produced by the inkjet method.
[0070] FIG. 4 is a micrograph of a hole transport layer 5 (Example 3) prepared by repeating the second step of coating twice using anisole as a solvent. The layer was prepared according to the above-mentioned preparation procedure except for the number of times of the second step. The white crystal in the center is the perovskite layer 4, and the layer formed on the surface of the perovskite layer 4 is the hole transport layer 5. A white line is drawn on the surface of the hole transport layer 5 to facilitate understanding of the drawing. The hole transport layer 5 according to this example has a thickness of 135 μm, and it was found to be formed uniformly. FIG. 5 is a micrograph of a hole transport layer 5 (Example 4) prepared by repeating the second step of coating four times using anisole as a solvent. A white line is drawn on the surface of the hole transport layer 5 to facilitate understanding of the drawing. The layer was prepared according to the above-mentioned preparation procedure except for the number of times of the second step. The hole transport layer 5 according to this example has a thickness of 378 μm, and it was found to be formed uniformly as in FIG. 4. In this way, it was found that the hole transport layer 5 can be formed uniformly by repeatedly applying the solution in which the hole transport material is dissolved in several portions.
[0071] In the above-described embodiment, the following configurations are envisaged. (1) A method for producing a hole transport layer 5 of a solar cell 10 having a perovskite compound, the method comprising the steps of: dissolving a hole transport material in a solvent having a flash point of 40° C. or higher and containing one or more selected from the group consisting of aromatic ethers, aromatic halides, and aromatic compounds having a condensed ring with an aliphatic ring; applying the solution containing the dissolved hole transport material to a surface of a perovskite layer 4; and drying the solution.
[0072] The hole transport layer 5 can be fabricated on the perovskite layer 4 by carrying out the steps of dissolving the hole transport material in a solvent containing an aromatic ether, an aromatic halide, or an aromatic compound having a condensed ring with an aliphatic ring and having a flash point of 40° C. or higher, applying the solution in which the hole transport material is dissolved to the perovskite layer 4, and drying the solution. In particular, since the flash point of the solvent is 40° C. or higher, in addition to the solution application method using the spin coating method, the solution can be applied using the inkjet method, and the hole transport layer 5 can be fabricated in a large area. Furthermore, since the solution can be selectively applied by using the inkjet method, it is also possible to partially fabricate the hole transport layer 5 on the perovskite layer 4.
[0073] (2) In the dissolving step described in (1), it is preferable that the amount of the hole transport material dissolved is 1% by mass or more and 5% by mass or less.
[0074] By setting the amount of the hole transport material to 1% by mass or more, the amount of the solvent in the solution can be reduced, which makes it easier for the solvent to volatilize in the drying step, reducing drying unevenness and smears caused by localized solvent volatilization, and enabling the production of a hole transport layer 5 with a uniform thickness. Furthermore, by setting the amount of the hole transport material to 5% by mass or less, the hole transport material can be made more easily soluble.
[0075] (3) In any of the coating steps described in (1) and (2), it is preferable to repeatedly coat the solution in multiple batches.
[0076] By repeatedly applying the solution in multiple portions, the solvent evaporates more easily than when the solution is applied all at once, which reduces drying unevenness, and thus makes it possible to produce a hole transport layer 5 with a uniform thickness.
[0077] (4) In any of the drying steps described in (1) to (3), it is preferable to dry the solution at a temperature of 50°C or higher and 120°C or lower.
[0078] Drying at a temperature of 50° C. or higher, at which the solvent does not volatilize instantly, can reduce localized solvent volatilization and produce a hole transport layer 5 with a uniform thickness. Furthermore, drying at a temperature of 120° C. or lower can suppress decomposition of the hole transport material.
[0079] (5) As any of the solvents described in (1) to (4), it is preferable to use anisole.
[0080] Among solvents with a flash point of 40° C. or higher, anisole is widely available on the market and is inexpensive, making it possible to efficiently and inexpensively fabricate the hole transport layer 5. In addition, since anisole is a highly volatile solvent, the solution applied onto the perovskite layer 4 dries easily, making it easy to fabricate the hole transport layer 5.
[0081] (6) The thickness of the hole transport layer 5 produced by any of the methods described in (1) to (5) above is preferably 75 nm or more and 400 nm or less.
[0082] If the thickness of the hole transport layer 5 is thinner than 75 nm, there is a concern that recombination may occur without going through the hole transport layer 5 due to pinholes or internal defects in the perovskite layer 4, resulting in a decrease in power generation efficiency. If the thickness of the hole transport layer 5 is thicker than 400 nm, the internal resistance in the hole transport layer 5 increases, making it difficult for holes that have moved from the perovskite layer 4 to the hole transport layer 5 to move to the electrode 6, which may lead to recombination and a decrease in power generation efficiency. Therefore, when the thickness of the hole transport layer 5 is 75 nm or more and 400 nm or less, the power generation efficiency is not decreased.
[0083] The solvent in which the hole transport material is dissolved is completely evaporated in the drying step, so no solvent remains in the hole transport layer 5 produced in this embodiment. Therefore, the solution cannot be identified from the structure of the hole transport layer 5.
[0084] Other embodiments In the above-described embodiment, the hole transport layer 5 is formed in a perovskite solar cell having an nip structure, but it may also be formed in a perovskite solar cell having a pin structure using a similar method. [Industrial Applicability]
[0085] The present invention can be widely used as a method for producing a hole transport layer of a solar cell. [Explanation of symbols]
[0086] 10: solar cell, 4: perovskite layer, 5: hole transport layer
Claims
1. A method for producing a hole transport layer of a solar cell having a perovskite compound, comprising the steps of: Dissolving a hole transport material in a solvent having a flash point of 40° C. or higher, the solvent including at least one selected from the group consisting of aromatic ethers, aromatic halides, and aromatic compounds having a condensed ring with an aliphatic ring; applying a solution of the hole transport material to a surface of the perovskite layer; and drying the solution.
2. In the dissolving step, The method for producing a hole transport layer according to claim 1 , wherein the amount of the hole transport material dissolved is from 1% by mass to 5% by mass.
3. In the applying step, The method for producing a hole transport layer according to claim 1 , wherein the solution is repeatedly applied in a plurality of separate steps.
4. In the drying step, The method for producing a hole transport layer according to claim 1 , wherein the solution is dried at a temperature of 50° C. or more and 120° C. or less.
5. The method for producing a hole transport layer according to claim 1 , wherein the solvent is anisole.
6. 6. A hole transport layer produced by the method according to claim 1, wherein the thickness of the hole transport layer is 75 nm or more and 400 nm or less.
Citation Information
Patent Citations
Perovskite type solar battery and manufacturing method of the same
JP2020136571A
Photoelectric conversion element and power generation device
JP2022149015A
Hole transport material and solar cell employing hole transport material
JP2023046046A